浅谈马来西亚华语词的外来语词 - Chong Ni Pei; Chong Pei Qi; Stephanie Tay Cin Wun (Journal of Chinese Language and Culture Studies, 2022)
Abstract: This paper is an attempt to analyze the lexical borrowing from foreign languages to Malaysian Chinese including English, Malay, Japanese and others. The English loanwords in Chinese accounted the most among them. This paper also discuss the cultural meanings contained by the loanwords, especially Malay loan words from which we are then able to explain the various cultural interactions between the Chinese and Malay community in Malaysia. We can also able to see the influences of English due to trace of British colonial era from the English loanwords. 摘要: 本文试图从外来语借此的角度分析马来西亚华人的语词使用情况。马来西亚华语受到源自英语、马来语、日语等影响，其中英语外来词所占的比例最大。本文还讨论了外来词所包含的文化含义，尤其是马来语外来词，从中我们能够解释马来西亚华人和马来社区之间的各种文化互动。我们还可以从英语借词中看到英国殖民时代的痕迹对英语的影响。